On the possibility of using hyperbaric oxygenation in the treatment of sars-cov-2 infected patients - Pavel Savilov (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
The article substantiates the feasibility of including Hyperbaric Oxygenation (HBO) in the treatment of patients infected with SARS-CoV-2. Possible mechanisms of therapeutic influence of hyperbaric oxygen on the course of the pathological process in the body of patients infected with SARS-CoV-2 are considered. The role of urea as a non-specific antioxidant adaptogen in the mechanisms of the therapeutic effect of HBO is considered. The important role of assessing the patient's condition at the time of oxygenation for the correct choice of modes and the number of HBO sessions is shown. It is concluded that it is appropriate to include in the therapy of SARS-CoV-2 infected patients with "soft" HBO regimens (1.3-2.0 ATA, isopression time 45-90 min), regardless of the degree and duration of hypoxemia.